Anti-inflammatory activity of bark of Xeromphis spinosa - Das, Biswa Nath; Saha, Achinto; Ahmed, Muniruddin (Bangladesh Journal of Pharmacology, 2008)
Thebark of Xeromphis spinosaextracted by a mixture of equal proportions of petroleum ether, ethyl acetate and methanol at an oral dose of 200 and 400 mg/kg body weight exhibited significant anti-inflammatory activity when compared with control.